Meeting climate goals through mitigation and intervention: developments in emissions reduction, greenhouse gas removal, and solar radiation modification - Dante McGrath; Hugh Hunt; John R. Taylor; Shaun Fitzgerald (Global Sustainability)
Abstract Non-technical summary This paper reviews efforts to meet the climate goals of the Paris Agreement: to limit global warming to well below 2°C and ideally to 1.5°C above pre-industrial levels. The paper shows how the likelihood of breaching these thresholds presents the need for additional measures, in mitigation and intervention. Three climate actions are discussed: emissions reduction, greenhouse gas removal, and solar radiation modification. These actions differ in timescale and current state of knowledge. Progress must intensify if they are to aid in securing a safe and stable climate for future generations. Technical summary Current assessments of global greenhouse gas emissions suggest the Paris Agreement temperature thresholds of 1.5°C and 2°C warming above pre-industrial levels could be breached. The impacts on humans and ecosystems could be severe. Global trends suggest a prolonged reliance on fossil fuels. Additional measures to limit global warming are therefore needed. Here, we review three climate actions: emissions reduction, greenhouse gas removal (GGR), and solar radiation modification (SRM). Emissions reduction requires shifting energy production away from fossil fuels (the primary contribution of anthropogenic greenhouse gas emissions), reducing energy use in key sectors, and optimising land management. GGR efforts must scale sustainably in the near term. The scale-up of novel methods is constrained by economic and technological challenges and, in some cases, limited knowledge. SRM has received growing attention, given the immediate impacts of global warming and the protracted timescales of emissions reduction and GGR. Robust research and governance frameworks are needed to assess the risks posed by SRM, alongside the risks of forgoing SRM. These three actions could enable society to fulfil the Paris Agreement, limiting global warming and its impacts while atmospheric greenhouse gas concentrations are reduced to sustainable levels. Social media summaryThe progress of climate mitigation and intervention towards securing a sustainable future in a safe and stable climate.